Measuring Alphavirus Fidelity Using Non-Infectious Virus Particles - Edward I. Patterson; Kamil Khanipov; Daniele M. Swetnam; Samantha Walsdorf; Tiffany F. Kautz; Saravanan Thangamani; Yuriy Fofanov; Naomi L. Forrester (Viruses, 2020)
Mutations are incorporated into the genomes of RNA viruses at an optimal frequency and altering this precise frequency has been proposed as a strategy to create live-attenuated vaccines. However, determining the effect of specific mutations that alter fidelity has been difficult because of the rapid selection of the virus population during replication. By deleting residues of the structural polyprotein PE2 cleavage site, E3Δ56-59, in Venezuelan equine encephalitis virus (VEEV) TC-83 vaccine strain, non-infectious virus particles were used to assess the effect of single mutations on mutation frequency without the interference of selection that results from multiple replication cycles. Next-generation sequencing analysis revealed a significantly lower frequency of transversion mutations and overall mutation frequency for the fidelity mutants compared to VEEV TC-83 E3Δ56-59. We demonstrate that deletion of the PE2 cleavage site halts virus infection while making the virus particles available for downstream sequencing. The conservation of the site will allow the evaluation of suspected fidelity mutants across alphaviruses of medical importance.